Specialty Store and Multi-Brand Store loyalty: An Indian consumer perspective - Singh, Sarabjot; Sinha, Piyush Kumar; Mishra, Hari Govind (ASEAN Marketing Journal, 2021)
In the competitive era of retailing, retailers need to understand the importance of store format preferences. The study aimed to understand consumer store loyalty; in-depth interview was conducted to examine consumer store loyalty antecedents for two retail formats: specialty stores and multi brand stores. The study conceptualizes store loyalty factors like program loyalty, trust and brand commitment. Trust and brand commitment act as mediating factors between store image and store loyalty formats, and also between brand image and store loyalty formats. The findings highlight how consumer store loyalty preference differ for these two formats.